Recontextualization of Islamic-Malay Ethics through Modern Zapin: A Didactic Analysis of Lesti Kejora's Song in Character Education - Fathin, Syarifah; Permadini, Susan (Journal of Malay Islamic Studies, 2025)
The erosion of cultural identity among Generation Z necessitates an innovative approach to character education through the recontextualization of local wisdom. This study aims to analyze the integration of moral and cultural values within the song "Zapin Melayu," a modern adaptation performed by Lesti Kejora, and evaluates its relevance as a pedagogical medium for character formation in contemporary education. Employing a qualitative descriptive design with content analysis, this research examines lyrical narratives and historical archives to interpret latent didactic messages. The findings reveal that "Zapin Melayu" serves as a sophisticated synthesis of Islamic theological principles and indigenous Malay ethics, encompassing themes of sincerity (ikhlas), social decorum (adab), and collective harmony. The results demonstrate that through its "dynamic packaging," this modern iteration successfully preserves the ontological essence of traditional art while resonating with modern musical sensibilities. Consequently, the song functions not merely as aesthetic entertainment but as a critical ethno-pedagogical tool that fosters spiritual awareness and social solidarity. This study concludes that the revitalization of traditional arts through contemporary media is imperative for fortifying national identity and internalizing akhlaqul karimah amidst the pressures of global homogenization.